Pratiques numériques, perception de la violence en ligne et victimation chez les étudiants - Julien Berthaud; Catherine Blaya (Recherches en Éducation)
Abroad, educational research has investigated peer violence perpetrated through electronic communication for several years. French research is just beginning. Tertiary education has little been studied in spite of a proceeding risk. This paper sets out to assess the extent of online victimization in higher education related to digital practices and students perception. Findings show evidence of the existence of the phenomenon among students, especially in association with their use of electronic communication. Moreover, perception gaps between science concepts and students views exist. This last finding is consistent with the known semantic and methodological debates about cyberbullying research.